Dopant‐Free Hole Transporting Materials for Perovskite Solar Cells. Issue 11 (27th September 2018) - Rezaee, Ehsan; Liu, Xiaoyuan; Hu, Qikun; Dong, Lei; Chen, Qian; Pan, Jia‐Hong; Xu, Zong‐Xiang
Abstract : This article reviews various dopant‐free hole transporting materials (HTMs) used in perovskite solar cells (PSCs) in three main categories including inorganic, polymeric, and small molecule HTMs. PSCs have undergone rapid progress, achieving power conversion efficiencies (PCEs) above 22%. With their low production cost and high efficiencies, PSCs are considered promising next‐generation solar cell technology. In all developed architectures for PSCs, including planar and mesoscopic with conventional and inverted structures, HTMs play a significant role in determining the photovoltaic performance of PSCs. Using p‐type dopants, however, is considered a common strategy to increase the hole conductivity of HTM, which is usually compensated by a more complicated fabrication procedure, higher production costs, and lower stability of PSC. Although several reviews on HTMs have been published, progress on dopant free HTMs needs to be reviewed and analyzed. Here, a review covering most of the published reports on dopant‐free HTMs is presented, and the device structure and fabrication method, HTM layer deposition techniques, and the efficiency and the stability of PSCs are addressed during discussions in each main category. Finally, an outlook on stability and PCE growth in PSCs based on dopant‐free HTMs is presented. Abstract : Dopant‐free hole transporting materials for perovskite solar cells are reviewed. The efficiency growth of perovskite solar cells (PSCs) based on dopant‐free hole transporting materials (HTMs) is highlighted. Hydrophilic chemical dopants can accelerate the degradation of the perovskite layer. Dopant‐free HTMs play a significant role in both efficiency and stability of PSCs.